Analysis of vehicle skidding potential on horizontal curves. (March 2021) - Peng, Jia; Chu, L.; Wang, Tangjie; Fwa, T.F.
Highlights: Three skidding modes on horizontal curves are analyzed. Computer simulation model predicts maximum safe speeds against skidding. Key skidding potential factors are vehicle speed, water depth, and pavement state. Other factors include curve radius, superelevation and vehicle parameters. Abstract: High crash rates on horizontal curves during wet weather are a major road safety concern. Among the various causes of crashes on horizontal curves, wet-weather skidding is a major contributing factor. This study analyzed the mechanisms of three possible modes of vehicle skidding on horizontal curves based on theories of mechanics. The three modes of skidding analyzed were: (i) forward skidding of front steering wheel, (ii) sideway skidding of front steering wheel, and (iii) sideway skidding of rear wheel. The main objective was to provide useful information to researchers and practitioners in identifying the important factors that contribute to horizontal curve crashes. A computer simulation procedure was developed to evaluate the maximum safe vehicle speeds against the three modes of skidding on wet horizontal curved pavements. This offers a much improved method for skidding potential evaluation compared to the conventional approximate method using estimated coefficient of friction. The skidding potential of a vehicle is defined as the difference between its speed and the maximum safe speed against skidding. The smaller the difference, the higher is the skidding potential. The relative magnitudes of skidding potential for the three skidding modes were considered for different operating conditions. Different operating conditions were represented by different values of pavement curve radii, super-elevations, and wet-weather conditions represented by the thickness of pavement surface water-film. The analysis identified five key factors that affect the skidding potential of vehicles negotiating a horizontal curve. They are: vehicle speed, curve radius, superelevation, water film thickness and pavement skid resistance state.